2014
DOI: 10.1186/1471-2466-14-42
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the CAT in the therapy assessment of COPD exacerbations in China

Abstract: Background: Chronic obstructive pulmonary disease (COPD) exacerbations are accompanied with increased systemic inflammation, which accelerate the pulmonary function injury and impair the quality of life. Prompt and effective treatments for COPD exacerbations slow down the disease progression, but an objective instrument to assess the efficacy of the treatments following COPD exacerbations is lacking nowadays. The COPD Assessment Test (CAT) is an 8-item questionnaire designed to assess and quantify health statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 33 publications
1
35
0
1
Order By: Relevance
“…Systemic inflammation is measured by plasma fibrinogen and serum CRP, which are increased in COPD and aggravated during exacerbations 11. Accordingly, several studies demonstrated that CRP is elevated corresponding to increased CAT score during exacerbations 6,13. In stable COPD, our study showed that CAT score is also independently associated with elevated serum CRP levels even after adjusting for confounding factors, although this statistical relationship is weak.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Systemic inflammation is measured by plasma fibrinogen and serum CRP, which are increased in COPD and aggravated during exacerbations 11. Accordingly, several studies demonstrated that CRP is elevated corresponding to increased CAT score during exacerbations 6,13. In stable COPD, our study showed that CAT score is also independently associated with elevated serum CRP levels even after adjusting for confounding factors, although this statistical relationship is weak.…”
Section: Discussionmentioning
confidence: 50%
“…Previous studies showed that this instrument provides reliable scores for predicting COPD exacerbation and severity, suggesting the CAT as a potential tool for the stratification of patients who are at risk for exacerbations 6,13,14. Systemic inflammation is measured by plasma fibrinogen and serum CRP, which are increased in COPD and aggravated during exacerbations 11.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This proposed parameter is significantly increased in patients during the progression of an exacerbation, as well as in patients with frequent exacerbations 22,38. The CAT scores, even during exacerbation, are increased in patients with a history of frequent exacerbations 39. Therefore, if the patient does not have increased symptoms (CAT score <10) and FEV 1 ≥50% of normal, prescription of one of the long-acting bronchodilators (LAMA or LABA) is recommended.…”
Section: Implementing the New Copd Algorithm For Copd Treatment In Rementioning
confidence: 99%
“…The CAT has good internal consistency and test–retest reliability;1 previous studies have shown its significance in diagnosis, response to therapies, and management both in stable and exacerbating COPD patients 48. CAT scores correlate well with important parameters of the disease, such as dyspnea grades, pulmonary function parameters, etc 79. Nowadays, it is widely used in clinical practice all over the world.…”
Section: Introductionmentioning
confidence: 99%